Fabricación de Recipientes a Presión Conforme a la Sección VIII, Div.1 del Código ASME - Rivera Mendoza, Orlando Rafael (My University, 2005)
Material Texting and Examination The basic material specification requires texting and examination of materials. The basic specification will reference the general delivery specification, SA-370 for any mechanical texting of steel products and E-30 for chemical analysis. The results of any tests will be recorded as required by the specification.
Keywords: Fabricación de recipientes a presión; Power boilers, fabrication codes, reference codes, Addenda, effects on fabrication flow, UW-12, UW-11, radiography, vessels, corrosion allowance, circumferential stress, welded pressure parts, class of materials, UG-11, UG-44 A.N.S.I Standards, UCS-6 plate material, welding qualifications of part ULT, carbon and low alloy steels, UCS-5, SA-285 chemical and physical requirements, UG-84 UG 77 material traceability, control of material during fabrication, material identification UG-93,forming, forming carbon steels, control of welding material, forming requirements, shell out of roundness, cold formed parts UCS-79, fiber elongation, (cutting, fitting and alignment), alignment of longitudinal joints, qualification of a W.P.S. UW-28, an unqualified W.P.S. UW-28, welding limitations, UW-35, qualification of welders and welding operators, UW-35 reinforcement, UHT-84 weld finish, general welding requirements, UW-40 P.W.H.T procedures